Corporate governance, accounting information quality, and cost of equity capital an Indonesia’ evidence - Krismiaji Krismiaji; Atmadi Raharja (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2018)
The purpose of this paper is to discuss empirical research examining the impact of corporate governance practice (CG) and accounting information quality (AIQ) on the cost of equity capital (COEC) in the context of agency problem and information asymmetry. This research uses a sample of 414 firms in the period between 2010 and 2013. The total observations consist of 1.656 firm-years. COEC, as a dependent variable is measured by price-earnings-growth (PEG) model. AIQ, as an independent variable is measured by absolute discretionary accrual as an inverse measure of accounting quality. CG is proxy by managerial ownership (MAN), measured by the percentage of management’s equity shares, and institutional ownership (INS) which is measured by the percentage of an institution's owned equity shares. The data used in this study is obtained from Indonesian Capital Market Directory, Indonesian Stock Exchange database, and from company annual reports. This research finds evidence of a negative association of AIQ and COEC. Since AIQ uses an inverse measure of accounting quality, this means that accounting quality increases COEC. Thus this result does not support the hypothesis. With respect to CG, both MAN and INS negatively affect COEC. This means that CG decreases COEC and support the hypothesis.